Exposure Draft 72 : financial reporting standard for small and medium-sized entities - Lembaga Piawaian Perakaunan Malaysia (Kuala Lumpur : Lembaga Piawaian Perakaunan Malaysia, 2010)
This Exposure Draft (ED) is issued by the Malaysian Accounting Standards Board for comment only. The recommendations in the Exposure Draft may be modified in the light of comments received before being issued in the form of a Financial Reporting Standard for Small and Medium-sized Entities.
Keywords: Financial statements -- Standards -- Malaysia; Accounting -- Standards -- Malaysia; Property -- Accounting -- Malaysia